Transient Stability Analysis and Post-Fault Restart Strategy for Current-Limited Grid-Forming Converter - Ziqian Zhang; Carina Lehmal; Philipp Hackl; Robert Schuerhuber (Energies, 2022)
Grid-forming converters are attracting attention for their significant advantages in terms of stability in a weak grid and simulated inertia. However, while they offer great flexibility due to the use of power semiconductors, they are also affected by their low current-carrying capacity. This means that during a fault, instead of the usual voltage control, a current limiting control is active, which changes the dynamic performance of the converter and influences transient stability. This manuscript focuses on the dynamic performance of grid-forming converters during the restart phase at the post-fault period, and proposes an initial phase threshold to prevent the converter from going into current saturation. Based on this, the manuscript proposes several restart strategies during the post-fault period, by using some fast resynchronization methods in order to meet the requirements of the converter’s stable operation and fast active power restoration. Finally, the above findings and the proposed strategies are validated by a joint control hardware-in-the-loop system.